Development of a 16S rRNA PCR-RFLP Assay for Bartonella Identification: Applicability in the Identification of Species Involved in Human Infections - Del Valle, Luis J. (2014)
Abstract We designed a 16S rRNA gene PCR-RFLP scheme to identify all currently described Bartonella spp. The 16S rRNA genes of all Bartonella spp. were in-silico analyzed in order to design a RFLP technique able to discriminate among different species. The restriction enzymes selected were MaeIII, MseI, Sau96I, BsaAI, DrdI, FokI, BssHII, BstUI, AluI, TspDTI and HphI which, according to a decision-making tree, facilitated the differentiation of all the currently described species of Bartonella.The technique was experimentally tested in different species of Bartonella, including human pathogenic B. bacilliformis and B. henselae with a 100% of concordance with the in-silico predicted patterns.This novel RFLP assay could be used to identify both human and non-human pathogenic Bartonella in diagnostic, phylogenetic and epidemiologic studies.